Guarantee of Legal Protection as a Principle of Lecturers’ Professionalism: The Moderating Role of Religiosity on the Influence of Emotional Regulation and Psychological Well-Being on Lecturers’ Work Engagement - Nurani, Nina; Rahmayanti, Rima; Salsabil, Imanirrahma (Faculty of Law, Universitas Pekalongan, 2024)
This study aims to understand the guarantee of legal protection as a principle of lecturers’ professionalism by developing and examining a model of the influence of emotional regulation and psychological well-being in influencing work engagement and lecturer performance, which is in line with the professionalism principle as a form of legal protection, in West Java Province. The moderating role of religiosity in Muslim and non-Muslim lecturers are also considered in influencing the level of interaction between variables. This study uses normative juridical and quantitative method. Normative juridical method is carried out by examining primary, secondary and tertiary legal materials, both documents and laws and regulations. For the quantitative study, 120 Muslim and non-Muslim lecturers are selected using purposive sampling. Data is distributed online and offline using Google Forms, then processed using Structural Equation Modeling-Partial Least Square (SEM-PLS) with SmartPLS software. The findings indicate that (1) the criteria for obtaining lecturer certificates are not yet comprehensive according to the role and position in the Teachers and Lecturers Law; and (2) the management of intellectual property rights (IPR) in universities is not yet optimal according to the legal protection of the results of creations and innovations in the IPR Law. Emotional regulation and psychological well-being influence work engagement, and work engagement has a positive influence on lecturer performance. The study also confirms the mediating role of work engagement and moderating role of religiosity within the relationship. This study provides insight of the guarantee of legal protection for the position, rights, and obligations along with recognition of lecturers in developing creativity and innovation in accordance with the principles of professionalism. This study also highlights the moderating role of religiosity by involving Muslim and non-Muslim participants in a cross-cultural context, thereby allowing a more comprehensive understanding of the influence of religiosity and cultural diversity on the variables studied.